Every grain of sand : Canadian perspectives on ecology and environment - Wainwright, J. A., 1946- (Waterloo, Ont. : Wilfrid Laurier University Press, 2004)
Annotation Combining personal memoirs with formal essays, this collection encourages activism as a personal commitment, dialogue with perceived enemies in environmental wars, and the dismantling of power-based divisions of centre versus marginal politics.
Annotation Universal in scope, yet focusing on recognizable Canadian places, this collection of essays connects individuals' love of nature to larger social issues, to cultural activities, and to sustainable technology. Subjects include activism in Cape Breton, eco-feminism, Native perspectives on the history of humans' relationship with the natural world, the inconsistency of humankind's affinity with nature alongside its capacity to destroy, and scientific and traditional accounts of evolution and how they can come together for the welfare of Earth's ecology.
World is your body / Lionel Rubinoff -- Growing roots in nature / Karen Krug -- Marginal world / Catriona Mortimer-Sandilands -- Reflections of a zealot / Elizabeth May -- Going home : memories of the natural world / J.A. Wainwright -- Who cares about the meadow? The changing conversation around religion and ecology / Anne Marie Dalton -- Romantic origins of environmentalism : Wordsworth and Shelley / Onno Oerlemans -- Wintergreen : reflections from Loon Lake, afterword / Monte Hummel -- Listening to our ancestors : rebuilding indigenous nations in the face of environmental destruction / Leanne Simpson -- Cutting a deal with Attila : confrontation, capitulation, and resolution in environmental conflict / Ehor Boyanowsky -- Romancing Labrador : the social construction of wilderness and the Labrador frontier / Peter Armitage -- Prey / Jarmo Jalava.
Includes bibliographical references.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Nature -- Effect of human beings on; Human ecology; Environmental degradation; Human ecology -- Canada; Environnement -- Dégradation.; Écologie humaine -- Canada; Écologie humaine; Êtres humains -- Influence sur la nature; human ecology; SOCIAL SCIENCE -- Human Geography; Nature -- Effect of human beings on; Human ecology; Environmental degradation; Environmental degradation; Human ecology; Nature -- Effect of human beings on; Canada